Behavioral Economics: Convergences between Economics and Psychology - Arizmendi Echecopar, Luis Felipe (2026)
The fundamentals of the authors and their contributions to Behavioral Economics are summarized, highlighting their convergence with psychology and their implications for economic theory and policy. A review of classical and contemporary economic literature (18th–21st centuries) is conducted, with an emphasis on the contributions of Smith, Hume, Mill, Bentham, Veblen, as well as Simon, Katona, Becker, Sen, Akerlof, Kahneman and Tversky, Vernon Smith, Shiller, Thaler, and their connections to the psychology of Skinner, Festinger, Mischel, Gilbert, Gigerenzer, Ariely, and Loewenstein. Advances that challenge the homo economicus model are systematized, showing how social norms, emotions, identities, and cognitive limits shape individual and market decisions, with applications in behavioral finance, welfare, and nudge-based public policy. It also discusses debates on replicability, external validity, ecological rationality, and institutions. It concludes that the integration of economics and psychology provides a series of more realistic descriptive microfoundations that are useful for guiding the design of public and private interventions.